Storage of ram semen in gelatin supplemented extender - Budai, Csilla; Egerszegi, István; Rátky, József; Kovács, András (Acta Agraria Debreceniensis, 2012)
The aim of our study was to examine how different gelatin concentrations affect ram semens viability in liquid storage at 5 oC for five days. Our hypothesis was if we add gelatin to the semen extender, than the viability of ram semen will be better in the extenders containing gelatin, than the control. We used two different semen extenders:1.5% UHT milk and 1.5% UHT milk + 5% egg yolk. We added 0; 0.5; 1.0; 1.5; 2.0% Dr. Oetker gelatin to the semen extenders. We stored the semen for five days at 5 oC and in every 24 hour we made sampling.We stained the smears with Kovács-Foote staining and evaluated them with light-microscope. We categorized the cells in five groups like: live and intact cells, live cells with injured acrosome, dead cells, live head with dead tail and live tail with dead head. We used one-way analysis of variance (ANOVA) to assign how gelatin concentration affects the number of the categorized cells. On the fifth day, the viability was the best in the following semen extenders: 1.5% fat UHT milk + 1.0% gelatin and 1.5% fat UHT milk + 1.5% gelatin, but it was not significant (p>0.05).